A Novel Damage State Simulation Method with Shape Memory Polymer - Du Jian-hua; Zhao Yang-dong (Communications - Scientific letters of the University of Zilina, 2009)
Shape Memory Polymer (SMP), a kind of smart materials which can memorize its former shape, has the general character of plastics and rubbers. The paper analyzes the present methods of damage simulation in numerical simulation and model test and performs mechanical test to study SMP’s shape memory mechanism as LgE-T. A new thinking is put forward to make the stiffness-controlled specimen according to the deficiency of present simulation methods, which could not simulate the damage process. The validating test proves the stiffness-controlled specimen can simulate the damage process of accumulation and has the value of validating the damage identification and structural safety evaluation algorithms.